2001
DOI: 10.1523/jneurosci.21-01-00169.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-XL–Caspase-9 Interactions in the Developing Nervous System: Evidence for Multiple Death Pathways

Abstract: Programmed cell death is critical for normal nervous system development and is regulated by Bcl-2 and Caspase family members. Targeted disruption of bcl-x L , an antiapoptotic bcl-2 gene family member, causes massive death of immature neurons in the developing nervous system whereas disruption of caspase-9, a proapoptotic caspase gene family member, leads to decreased neuronal apoptosis and neurodevelopmental abnormalities. To determine whether Bcl-X L and Caspase-9 interact in an obligate pathway of neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 33 publications
4
52
2
Order By: Relevance
“…Consistent with our previous studies, p53 7/7 neurons showed a marked attenuation and bcl-x 7/7 neurons a significant exacerbation of the effects of AraC on both caspase-3 activation and cell death ( Figure 1A,B). 18,21 Telencephalic neurons derived from bcl-x 7/7 /p53 7/7 embryos exhibited dramatic resistance to AraC-induced caspase-3 activation and death, equivalent to that observed in bcl-x +/+ /p53 7/7 telencephalic cultures ( Figure 1A,B). These findings suggest that AraC triggers a p53-dependent death pathway in telencephalic neurons that engages downstream Bcl-2 family mediated events including caspase-3 activation.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…Consistent with our previous studies, p53 7/7 neurons showed a marked attenuation and bcl-x 7/7 neurons a significant exacerbation of the effects of AraC on both caspase-3 activation and cell death ( Figure 1A,B). 18,21 Telencephalic neurons derived from bcl-x 7/7 /p53 7/7 embryos exhibited dramatic resistance to AraC-induced caspase-3 activation and death, equivalent to that observed in bcl-x +/+ /p53 7/7 telencephalic cultures ( Figure 1A,B). These findings suggest that AraC triggers a p53-dependent death pathway in telencephalic neurons that engages downstream Bcl-2 family mediated events including caspase-3 activation.…”
Section: Resultsmentioning
confidence: 60%
“…Consistent with our previous in vitro studies of DNA damage-induced neuronal death, Bcl-X L -deficient neurons showed increased, and p53-deficient neurons decreased, susceptibility to the death promoting effects of AraC, a known genotoxic agent. 18,21 p53 deficiency completely blocked the increased apoptotic susceptibility of Bcl-X L -deficient neurons to AraC and there was no difference in either caspase-3 activation or extent of death between bcl-x +/+ /p53 7/7 and bcl-x 7/7 /p53 7/7 neurons. These findings suggest that Bcl-X L lies downstream of p53 in the apoptotic pathway of DNA damage-induced death of telencephalic neurons.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations